Research progress on the role of bypass activation mechanisms in resistance to tyrosine kinase inhibitors in non-small cell lung cancer - Jiang, Ziyang; Gu, Zhihan; Yu, Xiaomin; Cheng, Tao; Liu, Bofu (Frontiers in Oncology, 2024)
The clinical application of small molecule tyrosine kinase inhibitors (TKIs) has significantly improved the quality of life and prognosis of patients with non-small cell lung cancer (NSCLC) carrying driver genes. However, resistance to TKI treatment is inevitable. Bypass signal activation is one of the important reasons for TKI resistance. Although TKI drugs inhibit downstream signaling pathways of driver genes, key signaling pathways within tumor cells can still be persistently activated through bypass routes such as MET gene amplification, EGFR gene amplification, and AXL activation. This continuous activation maintains tumor cell growth and proliferation, leading to TKI resistance. The fundamental strategy to treat TKI resistance mediated by bypass activation involves simultaneously inhibiting the activated bypass signals and the original driver gene signaling pathways. Some clinical trials based on this combined treatment approach have yielded promising preliminary results, offering more treatment options for NSCLC patients with TKI resistance. Additionally, early identification of resistance mechanisms through liquid biopsy, personalized targeted therapy against these mechanisms, and preemptive targeting of drug-tolerant persistent cells may provide NSCLC patients with more sustained and effective treatment.